A multiple criteria framework to evaluate bank branch potencial attractiveness - Ferreira, Fernando A. F. (2020)
Remarkable progress has occurred over the years in the performance evaluation of bank branches. Even though financial measures are usually considered the most important in assessing branch viability, we posit that insufficient attention has been given to other factors that affect the branches' potential profitability and attractiveness, such as: location features, trade area characteristics and facilities management. Based on the integrated use of cognitive maps and multiple criteria decision analysis, we propose a framework that adds value to the way that potential attractiveness criteria to assess bank branches are selected and to the way that the trade-offs among those criteria are obtained. This framework is the result of a process involving several directors from the five largest banks operating in Portugal, and follows a constructivist approach. Our findings suggest that the use of cognitive maps systematically identifies previously omitted criteria that may assess potential attractiveness. The use of multiple criteria techniques clarify and add transparency to the way trade-offs are dealt with. Advantages and disadvantages of the proposed framework are also discussed.